Hope in Action: Resilience and Adaptation to Climate Change at the Municipal Level in Massachusetts - Camille Washington-Ottombre; Una Soleil Elizabeth Fonte; Irina Jameron; Amandine Océane Lacroix (Transatlantica)
In the midst of grim narratives about climate change and dreadful climate projections, the Commonwealth of Massachusetts invited municipalities across the State as well as their residents to participate in the Municipal Vulnerability Preparedness (MVP) program whose goal is to plan for adaptation to climate change and enhanced resilience. Seven years after the launch of the MVP program, this work asked if the program succeeded in fostering “hope,” understood as the capacity to envision “the possibility for a favorable future” while planning for adaptation to climate change and resilience. To do so, we analyzed 334 planning reports and 233 action grants produced by municipalities throughout the Commonwealth. This research contributes to the literature on adaptation and resilience policies by providing the first comprehensive, aggregated case-study analysis of state-wide planning and action. As such, it highlights the value, limits, and room for improvement of such state-sponsored programs.This work shows that in many ways the MVP program is a success because it spread through the state, received very significant buy-in from municipalities, and placed adaptation to climate change and resilience at the heart of municipal action. Even though the MVP program has not yet fully transformed municipalities and readied them for climate change, it has reframed narratives around climate change and urban planning in Massachusetts and beyond. Whereas in many parts of Massachusetts municipalities had experienced a slow decline and abandonment by the state for decades, the MVP provided a new meaning to journey into an uncertain future characterized by climate change. It gave municipalities and residents a space as well as a reason to hope.